The compensation effect of civic education on political engagement: how civics classes make up for missing parental socialization - Neundorf, Anja; Niemi, Richard G.; Smets, Kaat (Springer, 2016)
The development of political engagement in early life is significant given its impact on political knowledge and participation. Analyses reveal a large influence of parents on their offspring’s curiosity about politics during their teenage years. Increasingly, civic education is also considered an important influence on political interest and orientations of young people as schools are assigned a crucial role in creating and maintaining civic equality. We study the effects of civic education on political engagement, focusing especially on whether and how civic education can compensate for missing parental political socialization. We use data from the Belgian Political Panel Study (2006-2011) and the U.S. Youth-Parent Socialization Panel Study (1965-1997), which both contain information on political attitudes and behaviors of adolescents and young adults, those of their parents, and on the educational curriculum of the young respondents. Our findings suggest that civics training in schools indeed compensates for inequalities in family socialization with respect to political engagement. This conclusion holds for two very different countries (the U.S. and Belgium), at very different points in time (the 1960s and the 2000s), and for a varying length of observation (youth to old age and impressionable years only).